Hadgarh Greenstone Belt: An extension of Tomka Daitari Greenstone Belt, Singhbhum Craton, India - Mousumi Bhattacharjee; Navratan Yadav; Saptarshi Mallick; Asutosh K. Tripathy; Suravi Banerjee (Geosystems and Geoenvironment, 2024)
Peripheral volcano sedimentary belts around the nucleus of Singhbhum-Granite-Complex are a part of one of the oldest continental crusts, known as the Singhbhum Craton (SC). Deciphering mutual relationship among these volcano-sedimentary packages offers considerable challenges. Badampahar-Gorumahisani Belt (BG Belt), Tomka Daitari Belt (TD Belt) and Bonai-Kendujhar Belt (BK Belt) draping Singhbhum-Granite-Complex as long linear belts from east, south and west, have some certain difference, primarily in terms of lithology. While the sedimentaries of BG Belt is mainly chemogenic, BK Belt is dominated by terrestrial sediments and TD Belt contains the both. Available data suggests the younger age of BK Belt than the rest couple of belts. Between TD Belt and BG Belt, another volcano sedimentary belt, commonly known as Hadgarh Belt, is present and it is less studied. The present study aims to characterize the Hadgarh Belt based on lithology and structure, which indicates its similarity with TD Belt. Almost identical lithologies are manifested by these two volcano sedimentary sequences barring the fact that the Hadgarh Belt has minor dominance of metasediments over metavolcanics, which is in subequal proportion in Tomka-Daitari and sensustricto BIF bands are absent in Hadgarh Belt. Both the belts have undergone uniform polyphase deformation and metamorphism. In both the belts, volcano sedimentary sequence of IOG is overlain by less deformed younger Mahagiri Quartzites and they are separated by an angular unconformity, marked by an impersistent conglomerate horizon. The intermediate area also sustains the similarities in depositional and deformational history with respect to the TD and Hadgarh belts on either side. Petrological studies also invoke similar mineral assemblage in the two belts, which is also in corroboration with the petrochemistry of the litho-units concerned. All the data thus generated, shows that the area, in totality, was evolved in an island arc setting varying from deep to shallow marine environments and sequence of deformations, intrusion of ultramafics followed by granite are also similar. In a nut shell, Hadgarh Belt can be referred as an extended part of the TD Belt.